The climate of cloud forests - Jarvis, Andy; Mulligan, M. (Wiley, 2011)
This chapter analyses the climatic conditions prevailing at sites where tropical montane cloud forests (TMCF) have been reported. Spatial data-sets of climate were used to describe the climate at 477 cloud forest sites identified by United Nations Environment Program (UNEP)-WCMC. Some 85% of the sites are found at altitudes between 400 and 2800 m a.s.l., with an average altitude of 1700 m. The range of altitudes at which cloud forests are found is extensive (220–5005 m). The climate of cloud forests is highly variable from site to site, with an average rainfall of ∼2000 mm year−1 and an average temperature of 17·7 °C. In addition, cloud forests are found in seasonal and aseasonal environments alike, both in terms of rainfall and temperature. There are some clear differences in the climates of cloud forests found in Africa, Latin America and the Caribbean, and those in Asia. Cloud forests are found to be wetter (with incident rainfall being 184 mm year−1 higher on average), cooler (by 4·2 °C on average), and less seasonally variable than other montane forests not affected significantly by fog and low cloud. Cloud forests are also almost completely confined to a zone within 350 km from the nearest coast. Finally, the climatic representativity of 14 intensively studied cloud forest sites (ISS) was analysed, as a group, the sites provided a fair representation of the climates found in cloud forests, evenly covering the ranges in temperature and rainfall. The majority of cloud forest sites occur in regions with 2000–2600 mm of rainfall and annual mean temperatures (Tmean) of 14–18 °C. Relatively dry cloud forest sites (<1000 mm of rain year−1) are under-represented in the UNEP-WCMC data-base.